Sexuality education and teacher training in Portugal - Teixeira, Filomena (2021)
In 2017 we started a study on sexuality education (SE) involving two Public Higher Education Institutions (HEI) with master's degree courses for kindergarten and primary education teachers in Portugal. The objectives of the study are: i) to determine if the study plans of teacher training (both for kindergarten and primary education teachers) of the different HEI include curricular units of SE; ii) to verify whether the legal framework in Portugal includes issues directly related to SE; iii) to identify specific contents of SE as part of curricular guidelines in pre-school and primary education; iv) to identify what knowledge, attitudes and behaviours about sexuality exist among future kindergarten and primary education teachers; and v) to develop and evaluate curricular proposals through the design of didactic resources to support educational practices that promote an integrated approach to the different dimensions of SE. In this free paper presentation, the results related to the first three objectives of the study will be presented and discussed. Although there is a legal framework in Portugal that integrates SE from the 1st to the 12th year of schooling, data analysis revealed that only a limited number of HEIs explicitly integrate curricular units directly associated with SE. In addition, the recent guidelines for curriculum support continue to give little or no relevance to the subject. Since kindergarten and primary education teacher training is the responsibility of HEIs, it is urgent to ask questions like these: 1. Are the teachers scientifically and pedagogically prepared to teach SE in schools? 2. How do HEIs plan to meet SE training needs? Is the political power conscious of the situation? Will there be a political will to think about SE strategies that involve schools, families and the community?